Bovine Model of Doxorubicin-Induced Cardiomyopathy. (30th December 2010) - Bartoli, Carlo R.; Brittian, Kenneth R.; Giridharan, Guruprasad A.; Koenig, Steven C.; Hamid, Tariq; Prabhu, Sumanth D.
Abstract : Left ventricular assist devices (LVADs) constitute a recent advance in heart failure (HF) therapeutics. As the rigorous experimental assessment of LVADs in HF requires large animal models, our objective was to develop a bovine model of cardiomyopathy. Male calves (n = 8 ) were used. Four animals received 1.2 mg/kg intravenous doxorubicin weekly for seven weeks and four separate animals were studied as controls. Doxorubicin-treated animals were followed with weekly echocardiography. Target LV dysfunction was defined as an ejection fraction ≤35%. Sixty days after initiating doxorubicin, a terminal study was performed to determine hemodynamic, histological, biochemical, and molecular parameters. All four doxorubicin-treated animals exhibited significant (P < 0.05 ) contractile dysfunction, with target LV dysfunction achieved in three animals. Doxorubicin-treated hearts exhibited significantly reduced coronary blood flow and interstitial fibrosis and significantly increased apoptosis and myocyte size. Gene expression of atrial natriuretic factor increased more than 3-fold. Plasma norepinephrine and epinephrine levels were significantly increased early and late during the development of cardiomyopathy, respectively. We conclude that sequential administration of intravenous doxorubicin in calves induces a cardiomyopathy with many phenotypic hallmarks of the failing human heart. This clinically-relevant model may be useful for testing pathophysiologic responses to LVADs in the context of HF.